Why Are (Financialised) Workers Becoming More Resigned and Conformist and Less Claimants? Empirical Evidence for Portugal - Barradas, R. (Dinâmia’CET-IUL Working Paper Nº 2023/03, 2023)
The deregulation and flexibilisation of labour relations has been on the active neoliberal agenda of policymakers all over the world, including in Portugal. Against this backdrop, labour conditions have been worsening since the 1970s and 1980s, and workers have progressively lost some labour rights, which is noticeable in stagnant (or falling) wages, the rise of personal income inequalities, the proliferation of atypical work, the increase of precariousness, the surge of emotional abuses in the workplace, the deterioration of work–life balance and the spread of informal work. Nonetheless, workers have evidenced higher resignation and conformism and lesser claimant behaviour in order to demand higher wages and better labour conditions, which is visible in the strong reduction in strike activity in the last four decades. Our argument asserts that workers’ financialisation and indebtedness levels restrain their demands for higher wages and better labour conditions due to the fear of decreasing their income and losing their jobs and the consequent risks of default. This paper aims to assess the relationship between workers’ financialisation and indebtedness levels and their strike activity by performing a time-series econometric analysis focused on Portugal during the period of 1979 to 2021. We conclude that workers’ financialisation and indebtedness levels have a negative effect on strike activity in Portugal, both in the short term and in the long term, especially on strike volume and strike duration. We also conclude that workers’ financialisation and indebtedness levels have been one of the main drivers behind the decline of strike activity in Portugal in the last four decades.